A Two-Phase Drone-Truck Optimization Framework for Patrolling and Thermal Comfort: Sustainable Hajj Safety - Shrouq Gamal; Mujahid N. Syed (IEEE Access)
The annual Hajj pilgrimage, attended by millions in the holy city of Mecca, Saudi Arabia, is characterized by extreme weather conditions and dense crowds, posing significant challenges in crowd management and thermal comfort. This study introduces a novel optimization framework for a drone-truck cooperative system designed to enhance thermal comfort during Hajj. The framework focuses on deploying drones to continuously monitor real-time data on air quality, temperature, humidity, and crowd conditions, followed by optimized responses to provide timely interventions. A key feature of the proposed framework is its integration of energy consumption and carbon emission considerations, aligning with sustainability and humanitarian objectives. The framework aims to minimize travel time and the total costs associated with truck and drone deployment, spraying material distribution, energy consumption, and carbon emissions. By simulating various scenarios in key Hajj locations-Arafat, Muzdalifah, and Mina Tent City-the study identifies optimal drone routing and deployment strategies to mitigate health risks associated with thermal stress and overcrowding. This research represents the first integration of drones, lab-on-drones, and spraying drones for thermal comfort enhancement during Hajj, promoting a safer and more environmentally sustainable pilgrimage experience. It underscores the transformative potential of technology in addressing critical public health challenges at large-scale, short-term, high-density events.